FROM BULBANCHA TO SHIKAAKWA: RAIL TOPONYMY IN AMERICAN SEMIQUINCENTENNIAL PLURALISM AND RESILIENCE - Purnama Rika Perdana; Najmi Hillalliyati; Jaelani Jaelani; Jamaluddin Nasution; Winaria Peggy. L Simanjuntak (Linguists : Journal of Linguistics and Language Teaching, 2026)
American transportation history is characterized by significant paradigm shifts, evolving from fragmented local waterways and roads into a sophisticated, interconnected system. This transformation has profoundly influenced the nation's cultural and linguistic landscapes, as expanding infrastructure often sought to supplant existing geographical identities with industrial and corporate narratives. This qualitative study investigates the toponymic evolution of the rail corridor in the City of New Orleans by comparing station data from the 1951 Illinois Central (IC) Railroad system map with the 2025/2026 Amtrak official route schedule. An analysis of the transition from 21 stops in 1951 Illinois Central to 20 stops in 2025 Amtrak reveals a complex stratification of names, where 19th-century corporate eponyms (such as McComb and Hazlehurst, named after railroad executives) are layered over an enduring indigenous and colonial substratum. Despite decades of corporate branding and institutional rebranding (such as the shift to Union Station), this research underscores a remarkable toponymic resilience among names deeply rooted in the physical landscape. The findings indicate that indigenous ecological and hydrological toponyms (such as Shikaakwa or Chicago, Teh-yak-ki-ki or Kankakee, and Yashu or Yazoo) have served as phonetic monuments, outlasting the transient nomenclature of private rail corporations. Ultimately, the City of New Orleans route functions as a moving archive of American pluralism, where the linguistic soul of the land endures beneath the shifting imprints of industrial progress.